Completing the data life cycle: using information management in macrosystems ecology research - Rüegg, Janine; Gries, Corinna; Bond-Lamberty, Ben; Bowen, Gabriel J.; Felzer, Benjamin S.; McIntyre, Nancy E.; Soranno, Patricia A.; Vanderbilt, Kristin L.; Weathers, Kathleen C. (My University, 2014)
An important goal of macrosystems ecology (MSE) research is to advance understanding of ecological systems at both fine and broad temporal and spatial scales. Our premise in this paper is that MSE projects require integrated information management at their inception. Such efforts will lead to improved communication and sharing of knowledge among diverse project participants, better science outcomes, and more transparent and accessible (ie “open”) science. We encourage researchers to “complete the data life cycle” by publishing well-documented datasets, thereby facilitating re-use of the data to answer new and different questions from the ones conceived by those involved in the original projects. The practice of documenting and submitting datasets to data repositories that are publicly accessible ensures that research results and data are available to and use-able by other researchers, thus fostering open science. However, ecologists are often unfamiliar with the requirements and information management tools for effectively preserving data and receive little institutional or professional incentive to do so. Here, we provide recommendations for achieving these ends and give examples from current MSE projects to demonstrate why information management is critical for ensuring that scientific results can be reproduced and that data can be shared for future use.
Keywords: Macrosystems ecology; Information management; Data life cycle